A review of laminitis in the donkey. (9th July 2021) - Thiemann, A. K.; Buil, J.; Rickards, K.; Sullivan, R. J.
Summary: Laminitis is a commonly occurring, painful condition of the foot that can have a major impact on the welfare of affected donkeys. When faced with a donkey suspected to have laminitis, the approach is broadly similar to that in the horse, however there are certain factors unique to donkeys that this article aims to highlight including: the differences in use, behaviour, anatomy, therapy and management.